Occurrence and infant exposure assessment of nitrates in baby foods marketed in the region of Lisbon, Portugal - Vasco, Elsa Reis (2019)
Commercial baby food labelled as from organic or conventional origin, including vegetable-based baby foods, fruit purees and fruit juices (n = 80), were analysed for nitrate content by an in-house validated HPLC method. Nitrate contents ranged from 5 to 230 mg kg−1 with a mean concentration of 102 mg kg−1 for vegetable-based baby foods, and a median of 5 mg kg−1 for both fruit purees and juices. One sample of vegetable-based baby food was higher than the legislated value (200 mg kg−1). There were no significant differences between average nitrate levels in analysed samples regarding both farming systems. The estimated nitrate intake through baby foods for a mean nitrate concentration of 47 mg kg−1 ranged between 0.5 (15% of ADI) and 1.3 mg kg−1 bw day−1 (35% of ADI). The ADI level was exceeded (107–146% of ADI) only for the 95th and 99th percentiles of nitrate concentration.